Convolutional neural network considering the effects of noise for bearing fault diagnosis - Han, Ilyoung; Chai, Jangbom; Lim, Chanwoo; Kim, Taeyun (International Conference on Nuclear Engineering, Proceedings, ICONE, 2020)
Convolutional Neural Network (CNN) is, in general, good at finding principal components of data. However, the characteristic components of the signals could often be obscured by system noise. Therefore, even though the CNN model is well-trained and predict with high accuracy, it may detect only the primary patterns of data which could be formed by system noise. They are, in fact, highly vulnerable to maintenance activities such as reassembly. In other words, CNN models could misdiagnose even with excellent performances. In this study, a novel method that combines the classification using CNN with the data preprocessing is proposed for bearing fault diagnosis. The proposed method is demonstrated by the following steps. First, training data is preprocessed so that the noise and the fault signature of the bearings are separated. Then, CNN models are developed and trained to learn significant features containing information of defects. Lastly, the CNN models are examined and validated whether they learn and extract the meaningful features or not.
Keywords: Bearing fault diagnosis; Data preprocessing; Fault signature; High-accuracy; Maintenance activity; Principal Components; System noise; Training data; Bearing fault diagnosis; Convolutional Neural Network (CNN); Machine diagnostics; Signal preprocessing